Cost of respiration energy in the larvae of Luciobarbus xanthopterus Heckel,1843 larvae artificially hatched in Basrah, Iraq. - Ahmed, Huda K.; Mohammed, Hanaa H.; Al-Mukhtar, Mustafa A.; Ali, Malik H. (Iraqi Journal of Aquaculture, 2019)
Artificial breeding of the native fish Luciobarbus xanthopterus Heckel was conducted for the first time in Basrah at the Marine Science Center’s hatchery (2009). We studied energy costs of the metabolic rate of the larval phase, during the period of 45 days, via the experimental laboratory measurements of the oxygen consumption rate at three temperatures 22, 26, 30 (C◦) coincided with the ambient water temperature in the rearing tanks (22.0-29.0 C◦). Direct significant (P < 0.05) positive linear correlations was estimated between time in days and both temperature (Y1) and fresh weight (Y2) of the larvae. Y1 = 0.0804 X +22.922 , R2 0.77, P < 0.05 Y2 = 1.2783 X -4.985 , R2 0.90, P < 0.05 The rate of oxygen consumption varied from 0.799 mg O2/ ind./d of the mass group (9.58) at 22 C◦, to 39. 36 mg O2 / ind./d of the mass group (35.0 mg) at 26 C◦, and declined to 29.16 mg O2/ ind./d of the mass group (35.0 mg) at 30 C◦, and the mass specific O2 consumption rate (metabolic rate M) varied from 3.170 mg O2/mg/d. to 1.121 mg O2/ mg/d and declined to 0.8304 mg O2/mg/d for the three groups respectively. The energy cost as estimated in cal./mg/d were varied from 2.27 for the period 1-5 days of their life to 1.056 cal./mg/d at the period 40-45 days of their life, and the daily energy costs of one larva was varied from 9.012 cal. during (1-5 days) to 43.041 cal. during days 35-40 of their life, the estimated values represent the routine metabolic rate level (RMR).